2009
DOI: 10.1016/j.jbiomech.2009.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Cells, growth factors and bioactive surface properties in a mechanobiological model of implant healing

Abstract: Interface conditions are of prime importance for implant fixation in the early post-operative period and modelling of specific biochemical interactions at implant surface is still missing. We hypothesized that updating osteoblast adhesion properties and growth factor source in an active zone located at the implant surface was relevant to model biochemical interactions of implant with its environment. We proposed an innovative set of diffusive-convective-reactive equations which relevant parameters were the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Computationally unwieldy models can occur even with simplified loading, simplified boundary conditions, simplified geometry and heterogeneity of tissue distribution and assumptions on the nature of the interface connections. While numerical models for predicting bone and tissue adaptation traditionally focus on mechanical and structural analysis, it is important to consider the contribution of other factors such as biologic and biochemical [36,37]. Incorporating complex mixed mechanics (solid þ fluid, poromechanics, reactive media) carries the challenge of providing rigorous validation on clinically relevant measures [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Computationally unwieldy models can occur even with simplified loading, simplified boundary conditions, simplified geometry and heterogeneity of tissue distribution and assumptions on the nature of the interface connections. While numerical models for predicting bone and tissue adaptation traditionally focus on mechanical and structural analysis, it is important to consider the contribution of other factors such as biologic and biochemical [36,37]. Incorporating complex mixed mechanics (solid þ fluid, poromechanics, reactive media) carries the challenge of providing rigorous validation on clinically relevant measures [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The theory inspired by works in implant fixation (Ambard and Swider, 2006;Gué rin et al, 2009) and tumors angiogenesis (Anderson and Chaplain, 1998) was completed by source terms to take into account the proliferation and diffusive terms to enhance the prediction of growth factor migrations. It was applied to a canine experimental model and extended by a parametric sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that sensitivity to surface topology is significant (Neidlinger-Wilke et al 1994;Fermor et al 1998;Pessková et al 2007) and generally, osteoblastic proliferation decreases when surface roughness increases (Martin et al 1995;Mustafa et al 2001;Rosa and Beloti 2003). We previously proposed a preliminary model of interactions with bioactive surfaces (Guérin et al 2009). Osteoblast adhesion properties and growth factor source were locally updated to model biochemical interactions of implant with its environment.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary model of local interactions with the implant bioactive surface of implant has been proposed (Guérin et al 2009) and this will be completed by relevant source terms involving the post-operative neovascularisation.…”
Section: Discussionmentioning
confidence: 99%